Given
![\begin{bmatrix}{3} & {-1} \\ {1} & {2}\end{bmatrix}\begin{bmatrix}{x} & {} \\ {y} & {}\end{bmatrix}=\begin{bmatrix}{8} & {} \\ {5} & {}\end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/nu9d0zyyc07d3rynjolcqum7hqv72o13zz.png)
Find
Rewrite as a system of equations in standard form.
Step-by-step explanation
![\begin{gathered} \begin{bmatrix}{3} & {-1} \\ {1} & {2}\end{bmatrix}\begin{bmatrix}{x} & {} \\ {y} & {}\end{bmatrix}=\begin{bmatrix}{8} & {} \\ {5} & {}\end{bmatrix} \\ \\ \begin{bmatrix}{3x-y} & {} \\ {x+2y} & {}\end{bmatrix}=\begin{bmatrix}{8} & {} \\ {5} & {}\end{bmatrix} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8er7bc40ssz9lwwkfyp01k0xtpf8l9pwf1.png)
so, ,
![\begin{gathered} 3x-y=8 \\ x+2y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/stmgh6v7c7j9bltb6meaqji0uzyd1cxlh6.png)
now check (6,10) is solution of both equations .
![\begin{gathered} 3(6)-10=8 \\ 18-10=8 \\ 8=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a9dfb4eqxjdefmcelh1o01k8gaadimvf5h.png)
hence , it is the solution of this equation.
now ,
![\begin{gathered} 6+2(10)=5 \\ 6+20=5 \\ 26\\e5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/he9tyow2uyj0o7v7wfgwbme90fhw22a3b9.png)
so , it is not solution of this equation.
Final Answer
The correct option is B